1980
DOI: 10.1177/000348948008900410
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malformations of the Ear Analysis of 94 Operations

Abstract: The 94 operations analyzed were performed on 80 ears in 73 patients with congenital malformation of the ear. Operative findings included 13 patients with a congenital absence of the oval window, 5 patients with vascular anomaly of the middle ear, and 6 patients with congenital cholesteatoma. Six of 13 patients with congenital absence of the oval window had a labyrinthotomy performed to create a new opening into the vestibule. The method of surgical repair in atresia was a canalplasty with fascia graft overlay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 1 publication
2
55
0
3
Order By: Relevance
“…The degree of microtia is parallel to the anomalous route of the facial nerve [13]. In our study, we observed that 28.1% of patients had facial canal dehiscence, while 2.9% of patients had temporary facial paralysis.…”
Section: Problems Concerning the Facial Nervesupporting
confidence: 47%
“…The degree of microtia is parallel to the anomalous route of the facial nerve [13]. In our study, we observed that 28.1% of patients had facial canal dehiscence, while 2.9% of patients had temporary facial paralysis.…”
Section: Problems Concerning the Facial Nervesupporting
confidence: 47%
“…Although congenital anomalies of the ossicles without malformations of the external ear are not common, high resolution CT scanning of the (2) 5b0Anterior and posterior crura fusion without oval window (1) 5c0No stapes and no oval window (2) 5d0No stapes and no oval window without incus long process (1) 5e0No stapes and no oval window with incus long process fused to promontrium (1) temporal bone and exploratory tympanotomy have increased their identification. Many prior studies [4,6Á12] have reported on congenital anomalies of the ossicles without deformities of the external ear in relation to their etiology and surgical results.…”
Section: Discussionmentioning
confidence: 99%
“…Minor congenital anomalies are restricted to the middle ear, while major congenital anomalies can involve the middle ear, external meatus, and the auricle [1,2]. Ossicular anomalies may occur with a normal tympanic membrane and external auditory canal.…”
Section: Introductionmentioning
confidence: 99%
“…The Jahrsdoerfer radiological scoring system, based on the findings of HRCT of the temporal bone and the appearance of the external ear, provides a very important preoperative guideline for selecting patients for canaloplasty and tympanoplasty [4][5][6][7] . However, the auditory ossicle and the canal for facial nerve are such fine structures that HRCT provides limited investigation of spatial relationships between the most important structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, accessing the ossicles during the operation is challenging, due to unpredictable anatomy and lack of valid intra-operative guidance. Although preoperative high-resolution computed tomography (HRCT) is routinely adopted to evaluate the malformation and make surgery plans, an unsatisfactory achievement ratio has been obtained [4][5][6][7] . This study is to radiologically investigate the spatial relationship between the TBR/CA and the ossicles, using the multi-planar reconstruction (MPR) technique, which allows reconstruction of HRCT views from any aspect, thus providing guidance for canaloplasty of the external auditory meatus and tympanoplasty operation.…”
Section: Introductionmentioning
confidence: 99%